2011
DOI: 10.1111/j.1600-0501.2011.02362.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of magnesium‐substituted nanohydroxyapatite coating on implant osseointegration

Abstract: Mg-substituted HA coated surfaces promote osteogenic differentiation of preosteoblasts in vitro and may improve implant osseointegration during the early stages of bone healing compared with pure EDHA coated surfaces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
58
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(65 citation statements)
references
References 35 publications
4
58
0
3
Order By: Relevance
“…36,37 It can promote hBMSCs or osteogenic cell proliferation as well as osteogenic differentiation. [38][39][40] In fact, Mg is found in natural enamel, dentine, and bone, and is associated with biologic apatite. Therefore, Mg is often incorporated into ceramics or adulterated into an alloy with other metal elements in order to promote osseous growth on implants.…”
mentioning
confidence: 99%
“…36,37 It can promote hBMSCs or osteogenic cell proliferation as well as osteogenic differentiation. [38][39][40] In fact, Mg is found in natural enamel, dentine, and bone, and is associated with biologic apatite. Therefore, Mg is often incorporated into ceramics or adulterated into an alloy with other metal elements in order to promote osseous growth on implants.…”
mentioning
confidence: 99%
“…The Mg containing calcium phosphates (MgCP), such as Mg substituted hydroxyapatite (Mg-HAP), has been shown as an attractive component to improve the biocompatibility of HAP coatings. For instance, Zhao et al [20] electrochemically deposited pure HAP and Mg-HAP coatings on the surface of pure titanium discs. They showed that the Mg-HAP…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Recently, growing interest has been devoted to a production of Mg containing biomaterials such as biocements [17], scaffolds [18] and coatings on metallic substrates [19][20][21] due to the beneficial biological effect of Mg emerging as a naturally occurring element in human body, especially in bones [22]. The Mg containing calcium phosphates (MgCP), such as Mg substituted hydroxyapatite (Mg-HAP), has been shown as an attractive component to improve the biocompatibility of HAP coatings.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Já suas propriedades quer químicas, mecânicas ou biológicas, mostram que este é um importante precurssor de hidroxiapatita conforme Zhao et al (2011). Outra propriedade diz respeito confirma a formação de sítios de biomineralização descritos por Gartner (2003) ao notarmos a presença de células osteoprogenitoras como os osteoblastos, osteócitos e osteoclastos.…”
Section: Discussionunclassified
“…O fosfato de cálcio amorfo sugere atender tais requisitos . Suas propriedades químicas, mecânicas ou biológicas, mostram que este é um importante produto para a formação de hidroxiapatita in vivo ou in vitro (ZHAO et al, 2011 (ROSEMBERG, 1996). E de 3 a 5% de moléculas não colágenas são responsáveis pela promoção de sítios ativos para a biomineralização e para a adesão celular.…”
unclassified